2010
DOI: 10.2174/092986710792231987
|View full text |Cite
|
Sign up to set email alerts
|

Development of Specific Inhibitors of CYP707A, a Key Enzyme in the Catabolism of Abscisic Acid

Abstract: Abscisic acid (ABA) is a plant hormone involved in stress tolerance, stomatal closure, seed dormancy, and other physiological events. Although ABA is registered as a farm chemical (plant growth regulator), its practical use has been limited, mainly due to its weak effect in field trials, which is considered to be due to its rapid inactivation through biodegradation. Catabolic inactivation of ABA is mainly controlled by ABA 8'-hydroxylase (CYP707A), which is the cytochrome P450 catalyzing the C8'-hydroxylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Similar approaches are currently also pursued in the plant sciences where antagonistic ABA analogs have been designed (Takeuchi et al, 2014), and pyrabactin variants are utilized as more stable and chemically unrelated ABA agonists (Overtveldt et al, 2015). An alternative treatment approach is to manipulate ABA homeostasis indirectly by targeting the different mechanisms that influence the levels of free intracellular ABA (Todoroki and Ueno, 2010). A conceptually similar approach has already been tried in animal systems by treatments with a herbicide (Fluridone), which is known to influence ABA levels in plants (Magnone et al, 2013).…”
Section: Physiological and Pharmacological Effects Of Aba In Animalsmentioning
confidence: 99%
“…Similar approaches are currently also pursued in the plant sciences where antagonistic ABA analogs have been designed (Takeuchi et al, 2014), and pyrabactin variants are utilized as more stable and chemically unrelated ABA agonists (Overtveldt et al, 2015). An alternative treatment approach is to manipulate ABA homeostasis indirectly by targeting the different mechanisms that influence the levels of free intracellular ABA (Todoroki and Ueno, 2010). A conceptually similar approach has already been tried in animal systems by treatments with a herbicide (Fluridone), which is known to influence ABA levels in plants (Magnone et al, 2013).…”
Section: Physiological and Pharmacological Effects Of Aba In Animalsmentioning
confidence: 99%
“…The expression levels of 5 genes involved in ABA biosynthesis [30][31][32], 4 genes involved in ABA catabolism [33,34], and 12 ABA-responsive genes were also checked in this study and some of them were used as positive controls. All AGI IDs were input into The Bio-Array Resource for Plant Biology (http://bar.utoronto.ca/) using the tool of "e-Northerns w. Expression Browser" [35].…”
Section: Affymetrix Microarray Data Analysismentioning
confidence: 99%
“…These studies showed important ABA functional groups for ABA J Plant Res (2011) 124:549-557 553 activities (Todoroki and Ueno 2010). Recently, the crystal structures of intercellular ABA receptors were reported Hubbard et al 2010), thus the results of SAR studies can be largely explained by the crystal structures of ABA receptors.…”
Section: Aba Probes For the Investigation Of Aba Binding Proteinsmentioning
confidence: 98%